Vom Viereck zum Schwarzen Quadrat - Ursula Klammer (Tr@jectoires)
Kazimir Malevič’s most famous painting was initially titled Quadrilateral when it was first presented. Only later was it given a new title and has since been known as Black Square. This essay examines the relationship between the painting and its title as two different yet contradictory levels of meaning in the artwork. The Black Square as a painterly “Urform” of Suprematism and cipher of the non-objective is – according to the thesis – the result of Malevič’s artistic theory, which already initiates a certain meaning with the title. This implicitly imposes a representational function on the work, which the pictorial form itself negates in its aesthetic reductiveness.